Diglossia in Literary Translation: Accommodation into Translation Theory - Zughoul, Muhammad; El-Badarien, Mohammed (Meta, 2004)
AbstractSociolinguistic research on varieties of language and language variation along with the necessity for meeting “equivalence” in terms of the appropriateness of the variety to the context have been well recognized in the formulation of a translation theory (Catford 1965, Crystal 1981, Newmark 1981 & 1988, and Mason 1990 among many others). However, the treatment of variation has always been restricted to “dialect” and has not encompassed the notion of diglossia. The delineation of equivalence in diglossic languages still begs for more questions than answers especially in literary translation where there is a continuous shift from one variety to another depending on the portrayal of characters and their interaction.